Fast authentication and data transfer scheme for massive NB-IoT devices in 3GPP 5G network - Cao, Jin (2020)
The emergence of narrowband Internet of Things (NB-IoT) has brought hope for the popularization and application of mobile Internet standards. Nowadays, NB-IoT technology has been introduced into the Third Generation Partnership Project (3GPP) standards, where low-overhead, low-data-transmission IoT devices can securely access the fifth generation (5G) core network through the 3GPP access network. However, according to the current 3GPP standard, these NB-IoT devices still employ the traditional authentication process of normal user equipment to implement mutual authentication between NB-IoT devices and 5G core networks, which brings a lot of communication and storage overhead, and it will be more serious when lots of NB-IoT devices are activated simultaneously. In this paper, we propose a fast mutual authentication and data transfer scheme for massive NB-IoT devices, which integrates the access authentication and secure data transmission process and achieves the authentications and data transmissions of a group of NB-IoT devices at the same time. Our scheme can not only greatly simplify the authentication process and alleviate the load of the networks but also ensure robust security protection including user anonymity and nonrepudiation. The performance analysis results show that the proposed scheme can withstand a variety of security attacks with ideal efficiency.